(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2022)
Currently, I am working in the field of tourism management in the UAE. My job is to communicate with tourists and when they ask me what country I am from, I can proudly say the name of my countr. I also have various meetings with professors and company leaders in the UAE. During my conversation, I improved my work skills. I am currently creating my own projects and I will introduce my new project to the tourism activity of Uzbekistan. These are certainly hundreds of meetings that are not accidental in my life’s journey to the top.